Importance and method of teaching biblical Hebrew and aramaic in religious education of children and adults - Roubalová, Marie; Kralik, Roman; Kondrla, Peter (Journal of Education Culture and Society, 2021)
Aim. The aim of this paper is to show and explain the meaning and the importance teaching biblical Hebrew and Aramic in religious education.  Method. The paper presents a descriptive study of philosophy of teaching Biblical Hebrew and Aramaic as an integral part of religious education, and at the same time it points out  the main problems of this education which are connected with the fact that the original language of the Tanakh (one of the basic textbooks for religious education) is not the native language of the students being taught  (even Israelis whose native language is Hebrew do not speak Biblical Hebrew) and studying it demands knowledge of Biblical Hebrew and Aramaic.Results. However, as the ideal method for teaching a foreign language does not exist, the choice of teaching methods must be based on the fact that each student or teacher prefers different method of work.